Quality of Life and Related Factors in Yazd in 2012 - Hossein Fallahzadeh; Mahdieh Momayyezi (Journal of Community Health Research, 2013)
Introduction: To compare the health status of different parts of the health indicators of quality of life is another factor. The purpose of this study is to assess the quality of life for people over 18 years of Yazd city. Materials and Methods: This descriptive cross-sectional study on 352 people over 18 years living in households was conducted in the city of Yazd in 1390. Cluster sampling was performed according to the Yazd city health center and for measuring quality of life WHOQOW-BREF questionnaire was used. Results: The mean (SD) domain scores of physical health12.99±2.76, mental health 12.99±2.76, public health, 13.15±2.92 and the environmental health 12.54±2.32, respectively. In the area of quality of life in people with chronic diseases to be significantly higher than healthy people (P <0.001). Quality of life scores in the physical health in men were higher than women. (P = 0.39) but no significant differences in other areas. The inverse relationship between BMI and quality of life score, and there was a direct correlation with income and housing infrastructure (P <0.05). Conclusion: The results of this study can be generalized to the population of Yazd is the quality of people's lives so it could be a good foundation for the city of Yazd in different areas. Meanwhile, the developed countries have a lower quality of life score is the most appropriate size in the population can help to improve quality of life.